Success Factors and Partnership Evaluation of Air–Rail Integration Development: A Case of a High-Speed Rail Project Linking Three Airports in Thailand - Waralee Rattanakijsuntorn; Benyapa Suwannarat; Nitchamol Samittivate; Chanuwat Nithikittiwat (Infrastructures, 2024)
As the air–rail integration continues to emerge around the globe, the successful and maintainable implementation of such schemes can be influenced by many factors within administrative, social, infrastructural, and economic aspects. With the existing airport rail link system that shifted from air–rail integration at beginning to air–rail cooperation at present, this work aims to assess the success factors of air–rail integration development in Thailand and evaluate the partnership level required to achieve a long-term and indefinite horizon of relationship based on an ongoing airport rail link project in the country. The factor assessment results from using fuzzy analytical hierarchy process (AHP) revealed different perspectives from regulators and operators, while directing the high influence of administrative, economic, and infrastructural factors. The partnership evaluation suggested the highest level of partnership; although, the operators still express doubt whether the competitive advantages incurred from the partnership and the partnership itself would be sustainable.
Keywords: Aviation Industry Analysis and Trends; Air Traffic Management and Optimization; International Law and Aviation